Secure Frequency Regulation of Electric Vehicle-connected Microgrid System under Multiple Latency Attacks. (July 2022) - Torabi-Farsani, Khashayar; Vafamand, Navid; Razavi-Far, Roozbeh; Saif, Mehrdad
Highlights: A robust μ-synthesis frequency regulator is proposed for AC MG systems with the V2G technology and latency attacks. Uncertainties and external disturbance inputs are considered and the controller is designed offline via numerical methods. The AC MG involves loads, wind and gas turbines, photovoltaic cells, diesel generators, and batteries. By using the Pade approximation, the latency attack is augmented to the state-space representation. Abstract: Occurring attacks in communication links of interconnected alternating current (AC) microgrids (MGs) is inevitable and interrupts the grid operation. If they are not tolerated, the stability of the overall AC MG may ruin. This paper deals with a robust (mixed) μ-synthesis-based controller to regulate the frequency in an AC MG system with vehicle-to-grid (V2G) technology. In the developed control method, the system uncertainties and external disturbance inputs are considered and the robust controller is designed offline based on a numerical method. The AC MG involves a load, a wind turbine, a photovoltaic cell, a gas turbine, a diesel generator, and a battery. The designed controller manipulates the diesel generator to mitigate the destructive effects of load, wind turbine, and photovoltaic cell power variations. By using the Pade approximation technique, the control input time delay is augmented to the state-space representation. Numerical comparisons are given to illustrate the superiority of the proposed control method. Graphical Abstract: Image, graphical abstract